DETERMINAN PROFITABILITAS, LIKUIDITAS DAN FINANCIAL DISTRESS TERHADAP RETURN SAHAM PERUSAHAAN INDEKS LQ45 - Inas Salsabila Putri, (2022)
The purpose of this study was to analyze the effect of the variables profitability, liquidity and financial distress on stock returns at LQ45 index companies listed on the Indonesia Stock Exchange in 2020-2021, because there are differences between real data and theory as well as research gaps in previous studies. The sampling method uses the purposive sampling method. The analysis technique used in this study was the Eviews Panel Data Regression Analysis version 12 and the Chow test, Hausman test, and Lagrange Multiplier test were performed to select the best test model. The results showed that (1) profitability proxied by Return On Assets (ROA) have no effect and no significant on stock returns, (2) liquidity proxied by Current Ratio (CR) have significant negative effect on stock returns, and (3) Financial distress calculated using the Taffler model have no effect and no significant on stock returns.